Association of VEGF cytokine levels and single nucleotide polymorphisms of the VEGF-A gene with the genital endometriosis in the female population of the Northwestern Federal District of Russia - Natalia V. Kulikova; Larisa S. Litvinova; Natalia V. Shperling; Andrei V. Ivanov (IP Berlin A.V., 2022)
Aim. To study the association of neoangiogenesis VEGF-A gene polymorphisms C(-460)T (rs833061), C(+936)T (rs3025039) with the risk of genital endometriosis in the population of the Northwestern Federal District; to examine the relationship of polymorphic variants of the VEGF-A neoangiogenesis gene C(-460)T (rs833061), C(+936)T (rs3025039) with the concentration of VEGF-A factor in the blood of females with genital endometriosis. Materials and methods. Eighty-five female volunteers aged from 19 to 44 (mean age 32.9 (5.8) years) with a histologically confirmed diagnosis of genital endometriosis were included in the stud; also, 79 females without endometriosis according to diagnostic laparoscopy for infertility or ectopic pregnancy, aged 20 to 42 (mean age 32.5 (7.2) years, p=0.71) were included in the study. The obtained data were analyzed using SPSS 20.0 statistical software package; 2 value and p value were estimated. Results. In our study, we found an association between the C allele and the CC genotype of the C(+936)T (rs3025039) polymorphism of the VEGF-A gene with genital endometriosis: odds ratio (OR) 2.35, 95% confidence interval (CI) 1.034.61, p=0.023; OR 1.89, 95% CI 1.034.61, p=0.048, respectively. The TT genotype of the C(-460)T (rs833061) polymorphisms and the TT genotype and the C(+936)T (rs3025039) allele of the VEGF-A gene were less common in patients with genital endometriosis: OR 0.43, 95% CI 0.141.29, p=0.023; OR 0.06, 95% CI 0.043.18, p=0.001; OR 0.43, 95% CI 0.231.29, p=0.023 respectively. The blood concentration of VEGF-A cytokine was lower in patients with genital endometriosis at all genotypes of C(-460)T (rs833061) locus of VEGF-A gene than that in females without endometriosis. The analysis of genotype frequency distribution of polymorphic site C(+936)T of the VEGF-A gene showed that the VEGF-A cytokine level was 1.5 times higher in the comparison group with heterozygous ST genotype versus that in homozygous genotypes. Enzyme immunoassay in the examined females showed a 2.5-fold decrease in the level of the VEGF-A angiogenic cytokine in blood serum in patients with endometriosis compared to those without endometriosis. Conclusion. To better understand the pathogenetic features of the endometriosis course and to make an individual prognosis of the course and therapy efficacy, an additional analysis of the associations between the polymorphisms of the listed genes and the angiogenesis factor level is required.